PENGARUH PERLAKUAN SORTASI, NATRIUM HIPOKLORIT DAN FUNGISIDA PADA KACANG TANAH UNTUK MENGELIMINASI KONTAMINASI ASPERGILLUS FLAVUS - Sholeh Avivi . (Universitas Lampung, 2005)
The Effect of Sorting, Sodium hypochloride (NaClO), and Fungicide Treatment on Peanut in Elimination the Aspergillus flavus Contamination. The humid tropical condition of Indonesia, the post harvest treatment, and the storage practices favour rapid growth and wide spread Aspergillus infestation on peanut. The objectives of this research was to find the best technique in controlling the Aspergillus infection on peanut. To achieve those objectives, complete randomised design in factorial with three factors was applied. The factors were grading and colour sorting (A1 = grading and colour sorting; A2 = without grading and colour sorting), NaClO blanching (B1 = without blanching; B2 = 1.25% NaClO blanching; B3=2.5% NaClO blanching), and Benlate T-20 WP treatment (C1 = 2,5 g/L; C2 = 3 g/L; C3 = 3,5 g/L). The result showed that the best combination treatment was A2B2C3 with the minimum amount of spore on peanut seed. With those combination treatment we concluded that the grading and colour sorting, the 1.25% NaClO blanching, and the application of 3,5 g/L Benlate T-20 WP could reduced the Aspergillus contamination up to 80% compare with A1B1C3 treatment.